Tagging Retrovirus Vectors with a Metal Binding Peptide and One-Step Purification by Immobilized Metal Affinity Chromatography - Ye, Kaiming (American Society for Microbiology, 2004)
Retroviral vectors produced from packaging cells are invariably contaminated by protein, nucleic acid, and other substances introduced in the manufacturing process. Elimination of these contaminants from retroviral vector preparations is helpful to reduce unwanted side effects, and purified vector preparations are desirable to improve reproducibility of therapeutic effect. Here we report a novel approach to engineer a metal binding peptide (MBP)-tagged murine leukemia virus (MuLV), allowing for one-step purification of retroviral vectors by immobilized metal affinity chromatography (IMAC). We inserted a His(6) peptide into an ecotropic envelope protein (Env) by replacing part of its hypervariable region sequence with a sequence encoding the His(6) peptide. Display of the His(6) tag on the surface of Env endowed the vectors with a high affinity for immobilized metal ions, such as nickel. We demonstrated that the His(6)-tagged MuLV could be produced to high titers and could be highly purified by one-step IMAC. The protein and DNA contaminants in the purified vector supernatants were below 7 μg/ml and 25 pg/ml, respectively, indicating a 1,229-fold reduction in protein contaminant level and a 6,800-fold reduction in DNA contaminant level. About 56% of the viral vectors were recovered in the IMAC purification. The purified vectors retained their functionality and infectivity. These results establish that an MBP can be functionally displayed on the surface of ecotropic retroviruses without interfering with their integrity, and MBP-tagged retroviral vectors can be highly purified by one-step IMAC.